2020
DOI: 10.1039/c9sm01084j
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale demixing in confluent biological tissues

Abstract: Surface tension governed by differential adhesion can drive fluid particle mixtures to segregate into distinct regions, i.e., demix. Does the same phenomenon occur in vertex models of confluent epithelial monolayers? Vertex models are different from particle models in that the interactions between the cells are shape-based, as opposed to metric-based. We investigate whether a disparity in cell shape or size alone is sufficient to drive demixing in bidisperse vertex model fluid mixtures. Surprisingly, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…In the latter case, we could even observe E-cad KO colonies surrounded by WT cells which could not be simply explained by the differential adhesion hypothesis and was not observed in previous adhesion based studies governed by cortical/line tension. 43,[45][46][47][48][49] We were able to replicate this in our simulations (Figure 6b). Moreover, to further test the unmixing phase we thought to probe the unmixing of two cell types with and without E-cadherin, but both showing extensile behaviour.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…In the latter case, we could even observe E-cad KO colonies surrounded by WT cells which could not be simply explained by the differential adhesion hypothesis and was not observed in previous adhesion based studies governed by cortical/line tension. 43,[45][46][47][48][49] We were able to replicate this in our simulations (Figure 6b). Moreover, to further test the unmixing phase we thought to probe the unmixing of two cell types with and without E-cadherin, but both showing extensile behaviour.…”
supporting
confidence: 63%
“…To this end, we first quantified the degree of phase separation by measuring the mixing-index of a mixture of WT and E-cad KO cells defined as the number of homotypic neighbours over the total number of cells. 46,47 In the segregation mechanism based on differential line tension this mixing-index grows with a power-law exponent with time and approaches one. 47 However, as evident from both experiments and simulations, the mixing-index in our system saturates and complete phase separation is never obtained (Figure 5a and b).…”
mentioning
confidence: 99%
“…Vertex models have recently received a lot of attention due to their potential in describing a wide range of tissue properties [25, 27, 36, 111-115, 117-119, 121-123]. Moreover, the accurate study of their mathematical properties revealed a plethora of interesting physical properties [27,28], such as second order rigidity [121], that could play a relevant role in the modeling of biological tissues. Importantly, these properties may imply an interesting departure from the framework proposed by inanimate material science, and proposes a theoretical framework that extends to biological materials.…”
Section: Cell-based and Energy Minimization In Vertex Modelsmentioning
confidence: 99%
“…Arguably, the response to an external stress will be, at least partially, driven by the possibility of cell rearrangements which, in turn, depend on the ease of movements of cells within the tissue. The energetic contributions that configure the overall energy of the tissue come from the resistance against compression and the departure from some preferred shape in cells which, in most cases, is introduced as the preferred relation perimeter/area in 2D projections [27,113,121,122]. Having N cells, the functional accounting for the energy of the (2D) system reads:…”
Section: Cell-based and Energy Minimization In Vertex Modelsmentioning
confidence: 99%
See 1 more Smart Citation